REFLECTING ON THE EXISTENCE OF CHRISTIAN EDUCATION IN INDONESIA - Aloysius Jondar; Donna Sampaleng (Bajang Institute, 2022)
The article, entitled The Existence of Christian Education in Indonesia, aims to understand the example of implementing Christian education which is growing in Indonesia. The analysis of the phenomenon of the implementation of the Christian education example refers to the concept of Christian education goals inherited by Martin Luther and the theory developed by Merril Evert about the implementation models of Christian education. The results of the author's research in this article are 1). Establishment of a Christian school with passion without capital support; 2). Establishment of Christian schools with money without being supported by conceptual knowledge of establishing Christian educational institutions; 3). Christian education institutions that are oriented towards hegemony (power) without having an orientation towards the development of quality education; 4) development of educational institutions that do not have professional human resources in dealing with educational administration. 5). Christian education with high spirituality is supported by very strong capital. The concept of Christian education that Martin Luther wanted was oriented towards understanding and knowledge of the word, attitudes based on the Bible, students, curriculum, libraries. This concept is always actual from time to time. And the contribution of Christian education in supporting development has become a part of showing its existence as a pluralist society in Indonesia